Animal-assisted therapy as a facilitator in care of institutionalised older women - Karine Eliel Stumm; Camila Neumaier Alves; Paulo Adão de Medeiros; Lúcia Beatriz Ressel (Universidade Federal de Santa Maria, 2012)
Objective: to report the experiences of Animal Assisted Therapy. Method: the development scenario of the project was a philanthropic Long Stay Institution to elderly, which aims to welcome and support elderly female, located in the city of Santa Maria. Results: as a direct benefit we realize the improvement of the elderly mood, beyond facilitating communication and interaction with the group, which valued the experience and brought benefits to the participants and professionals. Conclusions: considering the results of this interaction between animal and elderly, we seek to socialize this experience to encourage new projects that benefit and assist this population in depth study of this type of therapy